Vocational Education and Training for the Adolescents: Challenges and Opportunities - Vineeta Sirohi, (JOURNAL OF INDIAN EDUCATION, 2025)
Stepping into the threshold of vocation is the most crucial phase for an adolescent, as it creates a perpetual impact on the individual’s life. In view of the country’s demographic structure, characterising declining dependency ratio, demographic bulge and possessing youngest workforce offers an opportunity for India to become a reservoir of skilled workforce against the global manpower shortage. India’s transition into knowledge economy and the changing demands of the workplace requires new kinds of skilled workforce. The paper is an attempt to reflect on the opportunities and challenges posed by the global scenario and suggesting a paradigm change in the vocational education and training system in order to respond to the demand and supply mismatch of the workforce.